Legal Examination of Performance Oversight by the Papua People's Representative Council in Accordance with Community Aspirations Through the Mandate of the Special Autonomy Law - Wori, Herman; Ginting, Grenaldo; Polii, Johanis (LifeSciFi, 2023)
The enactment of Law No. 21 of 2001 concerning Special Autonomy for the Province of Papua reflects the political will of the Unitary State of the Republic of Indonesia towards the people of Papua. This decision is based on the consideration that the governance and development implementation in the province of Papua, while integrated with Indonesia, has not fully met the sense of justice, achieved prosperity, enforced the rule of law, and has not fully respected human rights, especially those of the indigenous Papuans. The legal research conducted in this study is normative legal research, focusing on examining norms or regulations related to the research object. Law No. 21 of 2001 concerning Special Autonomy for the Province of Papua represents the ideals and goals of the Unitary State of the Republic of Indonesia in building a fair, prosperous, and prosperous Papuan society based on Pancasila and the 1945 Constitution. The reality is that in the implementation of special autonomy, there are many deviations from the basic mandate of special autonomy. As a result, the Papuan people still feel left behind in a dilemmatic situation, unable to fully enjoy the benefits of special autonomy. This is because there is no significant improvement in welfare, peace conditions have not arrived, and basic rights are not adequately respected. The Papua Provincial People's Consultative Assembly (DPRP) is a regional representative institution that acts as an organ of the regional government in the province of Papua. The Papua People's Consultative Assembly has the task and authority to absorb, collect, accommodate, and follow up on the aspirations of the people. In accordance with the mandate of the Special Autonomy Law for the province of Papua, the Papua People's Consultative Assembly has the function of conveying the aspirations of the Papuan people regarding development and the expansion of new autonomous regions in the province of Papua to the People's Consultative Assembly (DPR RI).